The Effects of Assets and Debts on Profit Among Advertising, Printing and Media Listed Firms in Indonesia - Indah Mursalini, Wahyu; Maison, Witra; Sukraini, Juita; Anggraini Das, Nidia; ., Afniyeni (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the effect of assets and debts to company profit. Assets and Debts are the deciding variables to make a company profit. Debt is inversely proportional to profit. Therefore, any company’s management must be able to manage the assets and debt of the company to increase corporate profit. Need to explain why Sub Sector Company Advertising Printing and Media on Indonesia Stock Exchange is studies here. Based on the results of research, asset and debt have a significant effect to the profit of Sub Sector Company Advertising Printing and Media listed on Indonesia Stock Exchange. This is evidenced by statistical analysis. Â The researcher suggests the inclusion of control variables such as economic growth and capital structure so that the results of research can assist investors in assessing the company. Increase the period of research into 10 years, so that the results of research can describe the condition of the company for the long term and can pay attention to the business cycle. In addition, the study could be replicated on other sectors and comparative analysis could be done accordingly. Â Â